2001
DOI: 10.1111/j.1559-1816.2001.tb00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Congruent Mentoring: Predicting Asian American Student Participation Using the Theory of Reasoned Action1

Abstract: Predictors of Asian American first‐year college students’ intention to participate in a culturally congruent mentoring program was empirically documented using Ajzen and Fishbein's (1980) theory of reasoned action (TRA). Intention to participate was predicted by the belief that participation eases transition to college. Also, attitude toward participation was positively related to students’ beliefs that participation will strengthen ethnic identity and combat model‐minority myth. With 78% of students who inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A possible explanation is that a formal mentoring program as such might introduce the cultural conflict between individualism (seeking mentoring/help for oneself) and collectivism (fitting in with the ethnic group) for Asian American students. Another survey study showed that Asian American college students were more likely to participate in peer mentoring programs when these programs were designed to meet their needs (e.g., ease transition to college, strengthen ethnic identity, counter the model minority myth) (Kim, Goto, Bai, Kim, & Wong, 2001). In spite of the paucity of empirical research, findings from the above two studies suggest that Asian American college students have their psychosocial needs, face unique adjustment issues, and can benefit from mentoring programs that are compatible with their cultural values.…”
Section: Mentoring: a Culturally Incongruent Path To Success?mentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation is that a formal mentoring program as such might introduce the cultural conflict between individualism (seeking mentoring/help for oneself) and collectivism (fitting in with the ethnic group) for Asian American students. Another survey study showed that Asian American college students were more likely to participate in peer mentoring programs when these programs were designed to meet their needs (e.g., ease transition to college, strengthen ethnic identity, counter the model minority myth) (Kim, Goto, Bai, Kim, & Wong, 2001). In spite of the paucity of empirical research, findings from the above two studies suggest that Asian American college students have their psychosocial needs, face unique adjustment issues, and can benefit from mentoring programs that are compatible with their cultural values.…”
Section: Mentoring: a Culturally Incongruent Path To Success?mentioning
confidence: 99%
“…This stereotype may perpetuate the impression that Asian Americans have encountered very few barriers in higher education and that mentoring programs should be targeting other minority students who do not perform as well (Kodama, McEwen, Liang, & Lee, 2002). Also, the academic success of Asian Americans may mask the complete picture of their college experiences, excluding issues related to psychosocial adjustment and psychological well-being (Sandhu, 1997, Kim, Goto, Bai, Kim, & Wong, 2001). …”
Section: Model Minority Mythmentioning
confidence: 99%
See 1 more Smart Citation
“…Bai, Kim, & Wong, 2001;Thornburg & Pryor, 1998) and value-related issues (Dunlap, Grieneeks, & Rokeach, 1983;Oreg & Katz-Gerro, 2006). Valuerelated socialization effects may occur regardless of intentions, such as when academics teach theories with specific normative foundations (Ferraro, Pfeffer, & Sutton, 2005), but can be controlled and managed by business schools only if they are intentional.…”
mentioning
confidence: 99%
“…The widespread perception in mainstream American culture that Asian Americans enjoy high levels of achievement and general well-being, that is, the "model minority myth," has been previously discussed (e.g., Goto, 1999;Kim et al, 2001;S. Sue, Sue, Sue, & Takeuchi, 1995;Yoo, Burrola, & Steger, 2010).…”
Section: Cultural Stereotypesmentioning
confidence: 99%